2014
DOI: 10.3109/00498254.2014.920551
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of gastrointestinal absorption of digoxin involving influx and efflux transporter in rats: application ofmdr1aknockout (−/−) rats into absorption study of multiple transporter substrate

Abstract: 1.  This study was aimed to characterize gastrointestinal absorption of digoxin using wild-type (WT) and multidrug resistance protein 1a [mdr1a; P-glycoprotein (P-gp)] knockout (-/-) rats. 2.  In WT rats, the area under the plasma concentration-time curve (AUC) of oral digoxin increased after oral pretreatment with quinidine at 30 mg/kg compared with non-treatment, but the increasing ratio tended to decrease at a high dose of 100 mg/kg. In mdr1a (-/-) rats, however, quinidine pretreatment caused a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The role of intestinal transporters in the active uptake and efflux of drugs has been of increasing interest with growing knowledge of the expression, regulation, and activity of transporters . GLY is reported to be a substrate for rat P-gp as well as OATP, and the regional expression and activity of these transporters were included in the rat intestinal absorption model as described previously and in methods. For the in-house datasets, it was found that a decrease in the OATP activity improved the EOC of the predicted C – t profile.…”
Section: Discussionmentioning
confidence: 99%
“…The role of intestinal transporters in the active uptake and efflux of drugs has been of increasing interest with growing knowledge of the expression, regulation, and activity of transporters . GLY is reported to be a substrate for rat P-gp as well as OATP, and the regional expression and activity of these transporters were included in the rat intestinal absorption model as described previously and in methods. For the in-house datasets, it was found that a decrease in the OATP activity improved the EOC of the predicted C – t profile.…”
Section: Discussionmentioning
confidence: 99%
“…DGX is not only a substrate of P-gp, but also a substrate of an intestinal uptake transporter, Oatp1a5 [ 21 ]. In this study, the expression of Oatp1a5 might have been altered by CPT-11 treatment to affect the absorption of DGX.…”
Section: Discussionmentioning
confidence: 99%
“…DIG is known to be a P-gp substrate, whereas GLY relies on both Oatp and P-gp (El-Kattan and Varma, 2012;Estudante et al, 2013;Suzuki et al, 2014). Presence of food is reported to inhibit Oatp2b1, leading to PK differences between fasted and fed groups (Lee et al, 2020).…”
Section: Velocity Vel(x)mentioning
confidence: 99%
“…DIG is BCS class 4 and a P-glycoprotein (P-gp) substrate. GLY is BCS class 2 and a P-gp and organic anion transporter protein (Oatp) substrate (El-Kattan and Varma, 2012;Estudante et al, 2013;Suzuki et al, 2014). All datasets were collected at various feeding times postdose.…”
Section: Introductionmentioning
confidence: 99%